Botulinum neurotoxin formulations: overcoming the confusion - Samizadeh S; De Boulle K (Dove Medical Press, 2018)
Souphiyeh Samizadeh,1 Koenraad De Boulle2 1Great British Academy of Aesthetic Medicine, London, UK; 2Aalst Dermatology Clinic, Aalst, Belgium Abstract: Botulinum toxin A is produced by anaerobic spore-forming bacteria and is used for various therapeutic and cosmetic purposes. Botulinum toxin A injections are the most popular nonsurgical procedure worldwide. Despite an increased demand for botulinum toxin A injections, the clinical pharmacology and differences in formulation of commonly available products are poorly understood. The various products available in the market are unique and vary in terms of units, chemical properties, biological activities, and weight, and are therefore not interchangeable. For safe clinical practice and to achieve optimal results, the practitioners need to understand the clinical issues of potency, conversion ratio, and safety issues (toxin spread and immunogenicity). In this paper, the basic clinical pharmacology of botulinum toxin A and differences between onabotulinum toxin A, abobotulinum toxin A, and incobotulinum toxin A are discussed. Keywords: botulinum toxin, botulinum neurotoxin, moiety, protein complexes